Old-fashioned on purpose : cultivating a slower, more joyful life - Winger, Jill (Park Row Books, 2023)
Through engaging personal stories, history and lessons from life on the homestead, this inspiring and practical book shows us how doing things the old-fashioned way can help us find true happiness and meaningful connection--and unlock a powerful new sense of purpose.